P336 Association between the prior duration of remission and efficacy outcomes in patients with Ulcerative Colitis treated with tofacitinib 10 mg twice daily who were in stable remission and either dose-reduced to tofacitinib 5 mg twice daily or remained on 10 mg twice daily: 6-month data from the double-blind, randomised RIVETING study. (27th May 2021) - Dubinsky, M C; D'Haens, G R; Sandborn, W J; Ng, S C; Panés, J; Su, C; Lawendy, N; Lazariciu, I; Gardiner, S; Mundayat, R; Kulisek, N; Modesto, I; et al.
Abstract: Background: Tofacitinib is an oral, small molecule JAK inhibitor for the treatment of ulcerative colitis (UC). RIVETING (NCT03281304) is an ongoing, double-blind, randomised, parallel-group study designed to evaluate the efficacy and safety of dose reduction to tofacitinib 5 mg twice daily (BID) vs remaining on 10 mg BID in patients (pts) with UC in stable remission on tofacitinib 10 mg BID maintenance therapy. Eligible pts had received tofacitinib 10 mg BID for ≥2 consecutive years in an open-label, long-term extension study (NCT01470612), and had been in stable remission for ≥6 months (M) and corticosteroid-free for ≥4 weeks prior to enrolment. 1 We aimed to evaluate the association between the duration of remission prior to enrolment into RIVETING and the efficacy of tofacitinib 5 and 10 mg BID. Methods: Pts who were in partial Mayo score (PMS) remission (a PMS of ≤2 with no individual subscore >1, and a rectal bleeding subscore of 0) at RIVETING baseline were included in this analysis. Pts were randomised to dose-reduce to tofacitinib 5 mg BID or remain on 10 mg BID. We evaluated efficacy endpoints at Month 6 in RIVETING, stratified by duration of PMS remission (0–12, 12–24, 24–36, 36–48, >48 M) at RIVETING baseline. Results: At RIVETING baseline, 139 of 140 pts were in PMS remission: 69 pts dose-reduced to tofacitinib 5 mg BID and 70 pts remained on tofacitinib 10 mg BID. In both treatment groups, compared with pts with <24M of PMS remission, baseline modified Mayo and total Mayo scores were numerically lower in pts with a PMS remission duration of >24M; these pts also generally had a numerically lower change from baseline modified Mayo and total Mayo scores at Month 6 (Table). At Month 6, following dose reduction to tofacitinib 5 mg BID, PMS remission was maintained in 66.7%, 60.0%, 82.4%, 75.0% and 90.0% of pts with baseline PMS remission durations of 0–12M, 12–24M, 24–36M, 36–48M and >48M, respectively. Corresponding values for pts who continued to receive tofacitinib 10 mg BID were 80.0%, 88.9%, 91.7%, 100.0% and 100.0%. At Month 6, the proportion of pts achieving modified Mayo remission, remission and modified PMS remission was generally higher in pts with baseline PMS remission of >24M vs pts with PMS remission of <24M across treatment groups (Table). Conclusion: Following dose reduction from tofacitinib 10 to 5 mg BID, rates of modified Mayo remission, remission and PMS remission were numerically higher in pts with a PMS remission duration of >24M vs pts with <24M of PMS remission duration. The same trend was observed in pts who continued to receive tofacitinib 10 mg BID. These analyses are post hoc and limited by the small sample size. Reference: Vermeire et al. J Crohns Colitis 2020;Epub ahead of print